2022
DOI: 10.5858/arpa.2021-0411-oa
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers Can Predict Weaning From Acute Dialysis Therapy in Critically Ill Patients

Abstract: Context.— Critically ill patients with acute kidney injury (AKI) requiring renal replacement therapy (RRT) have a poor prognosis. Several urinary AKI biomarkers have been proposed to predict renal recovery, but with limited discriminatory ability. Objective.— To validate the predictive performances of novel biomarkers to identify which critical patients with AKI may successfully wean from RRT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…While this approach may not accurately capture the ongoing progression of AKI or incomplete renal recovery after AKI, recent research from the same database suggests that our approach likely had a low risk of bias ( 42 ). Nevertheless, subclinical AKI may be missed due to a lack of biomarkers other than sCr in the database ( 43 45 ). Third, community-acquired AKI may have been misdiagnosed as chronic kidney disease (CKD) due to our use of sCr data collected during admission, which could have led to an underestimation of the true incidence of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…While this approach may not accurately capture the ongoing progression of AKI or incomplete renal recovery after AKI, recent research from the same database suggests that our approach likely had a low risk of bias ( 42 ). Nevertheless, subclinical AKI may be missed due to a lack of biomarkers other than sCr in the database ( 43 45 ). Third, community-acquired AKI may have been misdiagnosed as chronic kidney disease (CKD) due to our use of sCr data collected during admission, which could have led to an underestimation of the true incidence of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) are markers of renal tubular injury [ 22 , 23 ], and insulin-like growth factor binding protein-2 (IGFBP-2) is also a novel marker for kidney inflammation [ 24 ]. The cytokine array results of kidney protein lysates showed that the levels of NGAL and IGFBP-2 in the kidneys of Kdm4c −/− mice were 1.5-fold higher than those of WT mice, which indicated that Kdm4c −/− mice had increased kidney inflammation after AKI compared with wild-type mice.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in canine FS, functional recovery of proximal tubules may be achieved even if the tissues are not completely repaired, and the degree of proximal tubular dysfunction may not necessarily be linked to the severity of tissue damage. A human report of critically ill patients with acute kidney injury demonstrated that a low urinary L-FABP level was an independent prognostic factor for weaning from renal replacement therapy ( Pan et al , 2022 ). Also, during follow-up of dogs with FS, urinary L-FABP may be a useful clinical marker to determine remission in conjunction with tubular function tests.…”
Section: Discussionmentioning
confidence: 99%